Perceptions of Kenyan Managers on Corporate Entrepreneurship and Innovation - Sylvia Naliaka, Wamalwa (2010)
The purpose of this study is to conduct an exploratory inquiry into the perceptions of Kenyan managers in regards to Corporate Entrepreneurship and managing innovation. This is mainly in response to the fact that studies on corporate entrepreneurship are still lacking, more so for firms in the developing world. This study will aim to uncover whether corporate entrepreneurship in developing countries is an imperative for success in today’s turbulent environment, as highlighted in literature which is based on studies from developed countries. Management perceptions were collected, measured and analysed using a written questionnaire survey comprising of open ended and close ended questions and also through telephone interviews. The respondents were a cross-section of senior level managers working in middle level companies based in Nairobi Kenya. The responses were analysed qualitatively through the use of matrix tables for the survey responses and breaking down the individual responses into themes as prescribed in phenomenology for the telephone interviews. The findings indicate that corporate entrepreneurship is important for the strategic renewal and continuation of the firm. Also, although there are similarities in perceptions of Kenyan managers and those identified in literature from the West, in terms of appropriate use of rewards, top management support supportive organizational structure; it is noted that resource constraints in Kenyan firms make prioritizing the three other antecedents of corporate entrepreneurship – availing resources, taking risks and tolerating failure difficult. A model for corporate entrepreneurship strategy in Kenyan firms is then proposed.